2011
DOI: 10.1182/blood-2011-01-326025
|View full text |Cite
|
Sign up to set email alerts
|

Do reactive oxygen species play a role in myeloid leukemias?

Abstract: Reactive oxygen species (ROS) are a heterogeneous group of molecules that are generated by mature myeloid cells during innate immune responses, and are also implicated in normal intracellular signaling. Excessive production of ROS (and/or a deficiency in antioxidant pathways) can lead to oxidative stress, a state that has been observed in several hematopoietic malignancies including acute and chronic myeloid leukemias (AML and CML). Currently it is unclear what the cause of oxidative stress might be and whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
199
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(203 citation statements)
references
References 146 publications
(173 reference statements)
2
199
0
2
Order By: Relevance
“…Thus, new therapies that more specifically target the molecular or metabolic abnormalities within leukemic cells have been highly sought. 28,29 In this study, we show that the mutation of W288 to cysteine sensitizes cells to oxidative stress induced by both bortezomib and ATO. In addition, the specific acquisition of a cysteine residue at position 288 appears to be responsible for the cytoplasmic accumulation of the most common variants of NPMc þ that contain the W288C mutation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, new therapies that more specifically target the molecular or metabolic abnormalities within leukemic cells have been highly sought. 28,29 In this study, we show that the mutation of W288 to cysteine sensitizes cells to oxidative stress induced by both bortezomib and ATO. In addition, the specific acquisition of a cysteine residue at position 288 appears to be responsible for the cytoplasmic accumulation of the most common variants of NPMc þ that contain the W288C mutation.…”
Section: Introductionmentioning
confidence: 99%
“…9,23 Arsenic trioxide (ATO) has emerged as the most active single agent in the treatment of acute promyelocytic leukemia, 24 and ATO-based therapies are being investigated in other cancers including other hematopoietic malignancies. [25][26][27][28][29] Although the mechanisms underlying ATO-induced cytotoxicity are not completely understood, ATO-mediated induction of ROS has been shown to reduce the membrane potential of mitochondria, enhance the release of cytochrome c and induce both caspasedependent and caspase-independent apoptosis. [30][31][32] AML has a poor prognosis in older patients, and intensive induction carries high morbidity and significant mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Increased ROS levels upon cytokine stimulation; low PRDX2 levels correlated with poor prognosis [29] A plethora of data has indicated alterations in ROS metabolism in leukemia, either linked to etiology, prognosis or therapy responses [30,31]. Many studies have supported the idea that ROS formation M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that cells expressing the ITD-mutated FLT3 generate higher levels of ROS (11)(12)(13). ROS, for example, H 2 O 2 , are considered to play an important role in cancers, including leukemia (14,15). Due to their DNA damaging properties, they are known to contribute to genomic instability.…”
mentioning
confidence: 99%